2018
DOI: 10.1128/aem.02430-17
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Dairy Cattle-Associated Escherichia coli Carrying bla CTX-M Genes in Washington State

Abstract: An increase in the prevalence of commensal carrying genes among dairy cattle was observed between 2008 and 2012 in Washington State. To study the molecular epidemiology of this change, we selected 126 -positive and 126-negative isolates for determinations of the multilocus sequence types (MLSTs) and antibiotic resistance phenotypes from obtained during a previous study. For 99 isolates, we also determined the alleles using PCR and sequencing and identified the replicon types of -carrying plasmids. The-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 59 publications
7
42
1
Order By: Relevance
“…The major ESBL families includes CTX-M, SHV, TEM, OXA and other variants. The bla CTX-M βlactamases group has been further divided into five sub groups, (bla CTX-M1 ,bla CTX-M-2 , bla CTX-M-8 ,bla CTX-M-9 , andbla CTX-M-25 ) and more than 120bla CTX-M enzymes have been reported (Afema et al, 2018). The success of bla CTX-M lineages has been credited to several factors, such as competent mobilization and distribution of CTX-M genes by mobile genetic elements MGEs (plasmids, transposon and insertion elements) (D'Andrea, Arena, Pallecchi, & Rossolini, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The major ESBL families includes CTX-M, SHV, TEM, OXA and other variants. The bla CTX-M βlactamases group has been further divided into five sub groups, (bla CTX-M1 ,bla CTX-M-2 , bla CTX-M-8 ,bla CTX-M-9 , andbla CTX-M-25 ) and more than 120bla CTX-M enzymes have been reported (Afema et al, 2018). The success of bla CTX-M lineages has been credited to several factors, such as competent mobilization and distribution of CTX-M genes by mobile genetic elements MGEs (plasmids, transposon and insertion elements) (D'Andrea, Arena, Pallecchi, & Rossolini, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The rise in the occurrence and spread of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli is currently a global emergency. These pathogens constitute a significant threat to the efficacy of many antimicrobials including 3 rd and 4 th generation cephalosporins [1,2]. Evidently, acquisition of antimicrobial resistance (AMR) genes arises due to continuous and indiscriminate use of antimicrobials in food animal production [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ten specific sets of primers (pir, udhA_2, silA, repB, repE, merA, sul3, floR, qnrS1, and bla TEM-1B [see Table S1 in the supplemental material]) designed to amplify the five modules from plasmid pSTB20-1T revealed that 3 isolates (THP14-1, THX8-2, and THX3-2; 7.3%) harbored all of the 9 tested genes, except for deletion of 1 gene silA in strain THX3-2. Of note, these 2 tet(X4)-carrying E. coli isolates and STB20-1 belonged to ST761, which was a predominant ST associated with dissemination of tet(X4) in our previous study (3) and bla CTX-M genes in other studies (11), although this ST seems to be uncommon overall and has been reported sporadically (12). These results indicate that there may be a low prevalence of pSTB20-1T-like plasmids in tet(X4)-carrying E. coli isolates, especially ST761.…”
mentioning
confidence: 48%